ZISMART : Platform Pembinaan Desa Sebagai Upaya Peningkatan Kesejahteraan Masyarakat Berbasis Digital Technology - Wahyu Kurnianingsish; Pandu Nur Wicaksono; Anis Choirun Nisa (CV. Ulil Albab Corp, 2022)
UMKM is a sector that is the backbone of the Indonesian economy. It is proven that the number of MSMEs in 2017 amounted to 62,922,617 units from 62,928,077 business units in Indonesia. However, from this very large number, 60% -70% of UMKM in Indonesia cannot access financing. Then Indonesia is the country with the largest number of mosques in the world, reaching 800,000. However, there are still many mosques that have not been managed properly, especially in the management of Zakat, Infaq, and Alms. In fact, if managed properly, the mosque's ZIS has the potential to be able to overcome UMKM financing problems. In addition, technological developments that are getting easier to reach also provide a role, where the management of this mosque can be done easily, effectively and efficiently through fintech. In this study, the authors provide the ZISMART innovation, which is a platform that bridges capital UMKM actors. Distribution to UMKM is also inseparable from the element of assistance, both UMKM in need economically and spiritually by KSEI volunteers as academics. With the existence of a community contract, all components that play a role in the distribution of these funds become clear and no one feels disadvantaged. The purpose of writing this paper is as a solution to the economic problems of the UMKM community through the pentahelix system which can help maximize the role of mosques for financing MSMEs, improving the welfare of the community and UMKM, and increasing Islamic financial literacy & inclusion in the UMKM sector. the author is a descriptive analysis with a qualitative approach.